2018
DOI: 10.1002/clc.23029
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial block as a predictor of atrial fibrillation in patients with ST‐segment elevation myocardial infarction

Abstract: IAB is common in patients with STEMI and along with the presence of diffuse coronary artery disease is associated with new onset of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Çinier et al 15 proposed IABs are prevalent in patients with STEMI and associated with the presence of diffuse coronary artery disease and new onset of AF. In our study, we focused on the presence of preoperative and postoperative (sixth month) IABs, their grades, and their associations with TAVIrelated factors among older adults with TAVI procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Çinier et al 15 proposed IABs are prevalent in patients with STEMI and associated with the presence of diffuse coronary artery disease and new onset of AF. In our study, we focused on the presence of preoperative and postoperative (sixth month) IABs, their grades, and their associations with TAVIrelated factors among older adults with TAVI procedure.…”
Section: Discussionmentioning
confidence: 99%
“…P-wave duration ≥120 ms with normal P-wave morphology is defined as partial IAB. In STEMI patients (n=198) without a history of atrial arrhythmias treated successfully with primary percutaneous coronary intervention (PCI), about half of the patients had partial or advanced IAB at presentation, while six hours after PCI, the prevalence of IAB had decreased to one quarter [8]. RCA stenosis and diffuse coronary artery disease were associated with IAB at admission.…”
Section: Interatrial Blockmentioning
confidence: 99%
“…Interatrial block (IAB) denotes a conduction delay between the right and left atria that manifests in a 12-lead electrocardiogram (ECG) as a P-wave duration of >120 ms. 10,11 A prolonged P-wave with biphasic (±) morphology in the inferior leads represents an even higher degree of IAB and has been referred to as advanced IAB. 10 The appearance of advanced IAB is frequently associated with atrial tachyarrhythmias, and has been found to predict AF in multiple clinical scenarios.…”
Section: Paroxysmal Atrial Fibrillation (Af) Occurs Frequently In Patmentioning
confidence: 99%
“…Interatrial block (IAB) denotes a conduction delay between the right and left atria that manifests in a 12‐lead electrocardiogram (ECG) as a P‐wave duration of >120 ms . A prolonged P‐wave with biphasic (±) morphology in the inferior leads represents an even higher degree of IAB and has been referred to as advanced IAB .…”
Section: Introductionmentioning
confidence: 99%